Forest School and its effect on the community: A brief review - Dabaja, Ziad; Yılmaz Uysal, Simge (PRISM: Casting New Light on Learning, Theory and Practice, 2022)
Forest School and similar outdoor nature-based education programmes have been spreading across different parts of the world. In this short manuscript, we draw on the literature to shed light on the demarcating characteristics of this distinctive form of outdoor education. Furthermore, we expand on the work by Dabaja (2022a; 2022b) to briefly introduce not only the impact of this educational concept on the involved children, but also the way it affects the educators and their pedagogies as well as the dynamics among the children’s family members and their connection to the outdoors. We then conclude by proposing a set of research-related recommendations to explore the full potentiality of the Forest School concept.